Symptoms reported by SARS-CoV-2 seropositive and seronegative healthcare and administrative employees in Denmark from May to August 2020. (August 2021) - Kaspersen, Kathrine Agergård; Greve, Thomas; Nielsen, Kent Jacob; Jespersen, Sanne; Mikkelsen, Susan; Vestergaard, Jesper Medom; Redder, Jacob Dvinge; Tolstrup, Martin; Thomsen, Marianne Kragh; Møller, Holger Jon; Østergaard, Lars; Kolstad, Henrik Albert; et al.
Highlights: The study included participants with mild and asymptomatic infections. The seroprevalence was 4% among 11 138 participants from Central Denmark Region. SARS-CoV-2-seropositive participants reported frequent COVID-19-associated symptoms. Loss of sense of taste and smell was the most frequently reported symptom. Symptoms were more likely to persist for more than 30 days among seropositives. Abstract: Background: The distribution and nature of symptoms among SARS-CoV-2 infected individuals need to be clarified. Methods: Between May and August 2020, 11 138 healthcare and administrative personnel from Central Denmark Region were tested for SARS-CoV-2 antibodies and subsequently completed a questionnaire. Symptom prevalence and overall duration for symptoms persisting for more than 30 days were calculated. Logistic regression models were used to estimate adjusted odds ratios (ORs) with 95% CIs. Results: In total, 447 (4%) of the participants were SARS-CoV-2-seropositive. Loss of sense of smell and taste was reported by 50% of seropositives compared with 3% of seronegatives. Additionally, seropositives more frequently reported fever, dyspnoea, muscle or joint ache, fatigue, cough, headache and sore throat, and they were more likely to report symptoms persisting for more than 30 days. In adjusted models, they had a higher risk of reporting symptoms, with the strongest association observed for loss of sense of taste and smell (OR = 35.6; 95% CI: 28.6–44.3). Conclusion: In this large study, SARS-CoV-2-seropositive participants reported COVID-19-associated symptoms more frequently than those who were seronegative, especially loss of sense of taste and smell. Overall, their symptoms were also more likely to persist for more than 30 days.